Integrated Transcriptomics and Metabolomics Analyses Provide Insights Into the Response of Chongyi Wild Mandarin to Candidatus Liberibacter Asiaticus Infection - Peng, Ting; Kang, Jing-Liang; Xiong, Xin-Ting; Cheng, Fang-Ting; Zhou, Xiao-Juan; Dai, Wen-Shan; Wang, Min; Li, Zhong-Yang; Su, Hua-Nan; Zhong, Ba-Lian (Frontiers in Plant Science, 2021)
Candidatus Liberibacter asiaticus (CLas) is the causal agent of Huanglongbing (HLB), which has caused great economic losses to the citrus industry. The molecular mechanism of host response to CLas in wild citrus germplasm has been less reported. Eighteen weeks after inoculation via grafting, all the CLas-inoculated Chongyi wild mandarin (Citrus reticulata) were positive and shown severe anatomical aberrations, suggesting its susceptibility to HLB. Transcriptomics and metabolomics analyses of leaves, barks and roots from mock-inoculated (control) and CLas-inoculated seedlings were performed. Comparative transcriptomics identified 3628, 3770 and 1716 differentially expressed genes (DEGs) between CLas-infected and healthy tissues in leaves, barks and roots, respectively. HLB tissues had higher transcripts per kilobase per million values and more genes that reached their maximal expression, suggesting that HLB might cause an overall increase in transcripts accumulation. But HLB-triggered transcriptional alteration shown tissue specificity. In CLas-infected leaves, many DEGs encoding immune receptors were down-regulated. In CLas-infected barks, nearly all the DEGs involved in signaling and plant-pathogen interaction were up-regulated. In CLas-infected roots, DEGs encoding enzymes or transporters involved in carotenoid biosynthesis and nitrogen metabolism were down-regulated. Metabolomics identified 71, 62 and 50 differentially accumulated metabolites (DAMs) in CLas-infected leaves, barks and roots, respectively. By associating DEGs with DAMs, nitrogen metabolism was the only pathway shared by three infected tissues, which was depressed in CLas-infected roots. In addition, 26 genes were determined as putative markers of CLas infection and a hypothesized model for HLB susceptibility mechanism in Chongyi was proposed. Our study may shed light on investigating the molecular mechanism of host response to CLas infection in wild citrus germplasm.